An impossible choice: knowing and not knowing in the Aviary (Theaetetus196c7-d2) - Edgar González-Varela (Revista Archai, 2022)
In this work I examine the "impossible choice" that Socrates poses to Theaetetus: to choose between accepting (a) that false judgment is impossible, or (b) that it is possible to know and not to know the same object (Theaetetus196c7-d2). According to the traditional interpretation, Socrates states that it is necessary to accept one of the two options: (b). Consequently, Plato would develop the Aviary as a model of explanation of error in which it is possible to know and not to know the same thing. Here I argueagainst this reading. I claim that Socrates says that the two options (a) and (b) must be rejected, and, therefore, that the Aviary presents a model in which false judgment is possible without accepting that it is possible to know and not to know the samething.